Validade de constructo clínico do diagnóstico de enfermagem ventilação espontânea prejudicada em crianças internadas em Unidade de Terapia Intensiva - Braga, Sara Teixeira (2024)
Studies that address the accuracy of defining characteristics (CD) can contribute to improving clinical reasoning, leading, therefore, to the formulation of nursing diagnoses that are more consistent with the patient's clinical situation. Given the above, the study aimed to determine the clinical construct validity of the nursing diagnosis of Impaired Spontaneous Ventilation in children with congenital heart disease admitted to the Intensive Care Unit (ICU). The sample included 71 children aged zero to two years, diagnosed with congenital heart disease. Data collection took place from January to August 2024, using a form developed by the researcher, namely: It referred to socio-demographic and clinical variables and the defining characteristics of the nursing diagnosis Impaired spontaneous ventilation. The data were compiled into Microsoft Excel 2010 software spreadsheets and were analyzed using the statistical package R version 4.2.1. The descriptive analysis of the data occurred by calculating absolute measures, percentages, measures of central tendency and dispersion. To analyze the accuracy of the clinical indicators of the nursing diagnosis Impaired spontaneous ventilation, the Latent Class Analysis Method was used, which allowed the identification of the prevalence of the diagnosis in children with congenital heart diseases, and the sensitivity and specificity values (accuracy measures ) of each clinical indicator investigated, with the respective 95% confidence intervals. It was found that the majority of children participating in the study were male (59.1%), also identifying that children without ventilatory support were five times more likely to have impaired spontaneous ventilation when compared to those who received this support (OR = 5.8; 95% CI: 1.1 – 29.3; Fisher test: p = 0.041). The other indicators were tested, however, they did not show a statistically significant relationship. Of the eleven defining characteristics, the most frequent for diagnosis stand out: increased heart rate (91.5%), blood gas changes (59.1%), and decreased O2 saturation (36.6%). The indicators: difficulty breathing, increased use of accessory muscles were considered sensitive and specific, making it possible to predict the diagnosis with greater accuracy. Regarding prevalence, the diagnosis under study was present in 9.9% of the population. Thus, the presence of this diagnosis in this clientele is highlighted, as well as the importance of correctly executing the diagnostic inference process and qualified assistance from nurses. Furthermore, it will be possible to provide faster and more accurate support for the nursing interventions necessary to obtain positive health outcomes in this context. In this way, it is considered that the process of measuring the accuracy of the nursing diagnosis Impaired spontaneous ventilation in children with congenital heart disease subsidized the refinement and improvement of this diagnosis and its clinical indicators. It is essential for nursing to take ownership of this diagnosis in the context of caring for children with heart disease.